Reformator i statysta albo hulaka na metafizyczną skalę. O dwóch portretach cara Iwana Groźnego w kinie rosyjskim - Szpulak, Andrzej (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
The text is an attempt to define the specificity of portraits of the first Russian Tsar, Ivan the Terrible, in the field of historiography and culture, including popular culture. This characteristic is referred then to the analysis of two films – S. Eisenstein's Ivan the Terrible (1944-1946) and P. Lungin’s Tsar (2009). These films depict two different interpretations of the historical figure presented above all in Russian discourse. On the one hand (Eisenstein), Ivan is seen as a prominent politician engaged in a state-building strategy; on the other (Lungin), he is above all a crazy criminal.

Tekst jest próbą określenia specyfiki portretu pierwszego cara rosyjskiego, Iwana Groźnego, na polu historiografii i kultury, w tym kultury popularnej. Charakterystyka ta odniesiona jest potem do analizy dwóch filmów – Iwana Groźnego S. Eisensteina (1944-46) oraz Cara P. Łungina (2009). Filmy te obrazują dwie różne interpretacje tej postaci historycznej obecne nade wszystko w dyskursie rosyjskim. Z jednej strony (Eisenstein) Iwan postrzegany jest jako wybitny polityk z państwowotwórczą strategią, z drugiej (Łungin) nade wszystko jako szalony zbrodniarz.
Reformer and Outstanding Politician or Rake on a Metaphysical Scale. Two Portraits of Tsar Ivan the Terrible in Russian Cinema
Keywords: Sergei Eisenstein; Pavel Lungin; Ivan the Terrible; the Russian film; historical film; the history of the film; Siergiej Eisenstein; Paweł Łungin; Iwan Groźny; film rosyjski; film historyczny; historia w kinie